2020
DOI: 10.3233/blc-200380
|View full text |Cite
|
Sign up to set email alerts
|

5α-Reductase Inhibitors Do Not Prevent the Development and Progression of Urothelial Cancer: In Vitro Evidence

Abstract: BACKGROUND: Androgen receptor (AR) activation has been implicated in the pathogenesis of urothelial cancer. However, it remains controversial whether 5α-reductase inhibitors (5α-RIs), which are known for blocking the conversion of testosterone to the more potent androgen dihydrotestosterone and often prescribed for the treatment of, for instance, benign prostatic hyperplasia, contribute to preventing the development of bladder cancer. OBJECTIVE: To determine the role of 5α-RI therapy in urothelial tumorigenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Despite these findings, the differential impact of different subtypes of androgen suppression modalities on BCa behaviour in preclinical models remains controversial. Indeed, in their in vitro study, Nagata et al demonstrated that, unlike androgen receptor antagonists, 5-ARIs have no significant impact on the development and progression of urothelial cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these findings, the differential impact of different subtypes of androgen suppression modalities on BCa behaviour in preclinical models remains controversial. Indeed, in their in vitro study, Nagata et al demonstrated that, unlike androgen receptor antagonists, 5-ARIs have no significant impact on the development and progression of urothelial cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to demonstrate an inhibitory effect on tumorigenesis by 5ARIs in vitro and in vivo have failed. 24,25…”
Section: Discussionmentioning
confidence: 96%
“…Efforts to demonstrate an inhibitory effect on tumorigenesis by 5ARIs in vitro and in vivo have failed. 24,25 Moschini et al performed a risk regression analysis of 196,914 patients with histologically confirmed localized prostate cancer identified in the Surveillance, Epidemiology, and End Results-Medicare insurance program linked database to examine whether patients who had received androgen deprivation therapy (34.7%) would have a lower incidence of BCa (1.3%). 13 The treated group and untreated group had similar risks of BCa incidence, leading the authors to conclude that ADT had no impact on BCa risk.…”
Section: Discussionmentioning
confidence: 99%
“…This was further confirmed by the promotion of the cell growth by MR knockdown. We then examined the potential downstream targets of MR that had been known to involve urothelial cancer outgrowth [20][21][22][23][24][25][26][27][28]. We found that the expression levels of MR in bladder cancer cells were positively and inversely associated with those of tumor suppressive E-cadherin and p53, and oncogenic molecules, including β-catenin, c-fos, and N-cadherin, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We next assessed the impact of MR signaling on the expression of several molecules known to involve urothelial cancer progression, including β-catenin [20,21], c-fos [22,23], E-cadherin [24,25], N-cadherin [25,26], and p53 [27,28]. Western blotting in control vs. MRknockdown sublines consistently demonstrated that the expression levels of MR was inversely or positively correlated with those of β-catenin/c-fos/N-cadherin or E-cadherin/p53, respectively (Figure 9).…”
Section: Expression Of Mr Vs Tumor Suppressor/oncogenic Proteins In B...mentioning
confidence: 99%